2005
DOI: 10.1620/tjem.206.219
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Lipoprotein Levels as a Guide for Clinical Severity in Patients with Idiopathic Dilated Cardiomyopathy

Abstract: Hyperlipidemia is a cardiovascular risk factor. In patients with idiopathic dilated cardiomyopathy (IDC), prognostic roles of endogenous lipoproteins are not fully clarified. It has been known that there is a direct relationship between the levels of cytokines (tumor necrosis factor-α [TNF-α ] and interleukin-6 [IL-6]) and deteriorating functional classes of heart failure and mortality. The present study compared the levels of circulating TNF-α , IL-6, lipoproteins, and apolipoproteins in patients with stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…We have found that patients with impaired CFR have lower total cholesterol, LDL cholesterol, and triglyceride values in accordance with a study by Sezgin et al [12], which reported that decreased lipoprotein concentrations in patients with IDC indicate poorer prognosis.…”
Section: Resultssupporting
confidence: 92%
“…We have found that patients with impaired CFR have lower total cholesterol, LDL cholesterol, and triglyceride values in accordance with a study by Sezgin et al [12], which reported that decreased lipoprotein concentrations in patients with IDC indicate poorer prognosis.…”
Section: Resultssupporting
confidence: 92%
“…Apolipoproteins A1 (APOA1), A4 (APOA4) and C3 (APOC3), which are lipid-binding proteins involved in the transport of lipids in plasma, were found to be down-regulated in iDCM compared to control serum in our study. Lower plasma APOA1 levels were also found in human patients with iDCM compared to controls [29,33]. APOA1 is a major constituent of high-density lipoprotein particles which was found to have anti-inflammatory properties since it may interfere with the assembly of complement C9 of the MAC of complement cascade [34].…”
Section: Discussionmentioning
confidence: 96%
“…In patients with established heart failure, the role of low HDL and/or low apolipoprotein A1 in predicting heart failure events as well as mortality has been demonstrated17-20, even in those with non-ischemic etiologies21. While most have speculated the primary contribution of HDL’s favorable effects is via its reverse cholesterol transport properties, other anti-inflammatory, anti-apoptotic, and anti-thrombotic effects of HDL can also play important roles as evidenced by with its inverse relationship with inflammatory mediators22, 23.…”
Section: Discussionmentioning
confidence: 99%